2002
DOI: 10.1074/jbc.m110865200
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Coactivator Function by Coactivator-associated Arginine Methyltransferase (CARM) 1 and β-Catenin with Two Different Classes of DNA-binding Transcriptional Activators

Abstract: The androgen receptor (AR) binds to and activates transcription of specific genes in response to its cognate steroid hormone, dihydrotestosterone. Transcriptional activation by the DNA-bound AR is accomplished with the help of a variety of coactivator proteins. For example, the p160 coactivators bind directly to AR and recruit additional coactivators such as the histone acetyltransferase p300 and the histone methyltransferase CARM1. The current study tested whether CARM1 can cooperate with other types of coact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
113
0
1

Year Published

2003
2003
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(116 citation statements)
references
References 33 publications
2
113
0
1
Order By: Relevance
“…Accordingly, reporter gene assays showed that CARM1 acts as a potent transcriptional coactivator of the CCNE1 gene and of other G 1 ͞S-regulated genes (DHFR, cdc6), together with E2F͞DP and by way of the E2F sites present in these promoters. This result is consistent with recent reports showing that the CARM1 transcriptional coactivating function is not restricted to nuclear receptors, but that it also associates and cooperates with p53, NF-B, and LEF1͞TCF4 (29)(30)(31). Thus, this ubiquitously expressed enzyme is likely to have a more pleiotropic function than was originally thought, notably in the control of the cell cycle and survival.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Accordingly, reporter gene assays showed that CARM1 acts as a potent transcriptional coactivator of the CCNE1 gene and of other G 1 ͞S-regulated genes (DHFR, cdc6), together with E2F͞DP and by way of the E2F sites present in these promoters. This result is consistent with recent reports showing that the CARM1 transcriptional coactivating function is not restricted to nuclear receptors, but that it also associates and cooperates with p53, NF-B, and LEF1͞TCF4 (29)(30)(31). Thus, this ubiquitously expressed enzyme is likely to have a more pleiotropic function than was originally thought, notably in the control of the cell cycle and survival.…”
Section: Discussionsupporting
confidence: 81%
“…Consistent with this function, CARM1 recruitment at nuclear receptor-responsive genes was found to coincide with their activation (23,24,(26)(27)(28)(29) and with histone H3-R17-and H3-R26-specific methylations of their promoter region (23,24,(26)(27)(28)(29). More recently, CARM1 was also found to associate and cooperate with p53, NF-B and LEF1͞TCF4 (29,31,32), suggesting that this enzyme plays pleiotropic roles in cell proliferation and survival. Here, we show that CARM1 acts as a potent coactivator for the CCNE1 gene together with ACTR and through E2F sites.…”
mentioning
confidence: 62%
See 1 more Smart Citation
“…b-Catenin binds to the activation function 2 region within the N-terminal domain of liganded hAR protein and augments liganddependent hAR transcriptional activity in PCa cells (Song et al, 2003). The coactivator function of b-catenin likely involves increased recruitment of p160 coactivator proteins as well as tertiary proteins, such as histone methyltransferase (Koh et al, 2002). b-Catenin also alters ligand specificity of hAR-mediated transcription, enhancing transcriptional activation by androstenedione and estradiol and diminishing antagonism by bicalutamide (Truica et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The opposite observation has been made for H3 methylation, where prior acetylation of H3 by CREB-binding protein (CBP) facilitates its methylation by CARM1 (17). CARM1's coactivator activity is not dedicated to transactivated steroid receptors but also functions with the myogenic transcription factor mouse embryonic fibroblast (MEF) 2C (18) and ␤-catenin (19). Chromatin immunoprecipitation analysis has shown that histone H3 becomes methylated in vivo on Arg-17 at the estrogen receptor-regulated pS2 gene (20) and at a genome integrated mouse mammary tumor virus (MMTV) reporter (21), and this methylation coincides with the presence of CARM1.…”
mentioning
confidence: 99%